A Modified UTAUT Model for Hospital Information Systems Geared Towards Motivating Patient Loyalty - Alismaili S.N.R.; Shanmugam M.; Kasim H.A.; Magalingam P. (Springer Science and Business Media Deutschland GmbH, 2023)
Hospitals; Information systems; Information use; Motivation; Tourism; Configurability; Ease-of-use; Empirical studies; Healthcare services; Hospital information systems; Patient loyalties; The unified theory of acceptance and use of technology(UTAUT); Utaut models; Medical computing